Controle de doenças de final de ciclo e oídio da soja por extratos aquosos de Cymbopogom citratus, Rosmarinus officinalis e Curcuma longa e solução de curcumina - Becker, Andrea (2005)
The occurrence of late season leaf diseases (DFC) caused by Septoria glycines and Cercospora kikuchii and powdery mildew caused by Microsphaera diffusa in soybean (Glycine max) are easily identified in field. In recent years, there has been a seach for alternatives to fungicides that provide satisfactory disease control with low environmental impact and low toxicity to human. The objective of this study was to evaluate the effect of extract of C. citratus, R. officinalis and C. longa and by curcumin solutions, to control DFC and powdery mildew. In vitro assays were conduced to verify the antimicrobial activity of those plant extracts, by evaluation of the mycelial growth of C. kikuchii in PDA medium. Additionally, assays under field conditions were carried out with soybean cv. CD 215. The pyraclostrobin + epoxiconazole fungicide (0,6 L c.p. ha 1) was used as control. Extract of C. citratus inhibited the mycelial growth of C. kikuchii in 36,9%, to concenttrations up to 10% of the extract. To R. officinalis, the inhibited was 42,8% to concentration 10%. The lower antimicrobial activity was with C. longa with 17,9% of inhibition concentration 20%. In relation to field assays extract of C. longa 5% was higher than the control with water to the weight of one hundred seeds, like as C. citratus 5% and R. officinalis 5 and 10 %. The production of the extract of C. longa at 10% was 3856 kg ha-1 with good control of diseases. R. officinalis at 5% showed production higher than the control with water. Those two treatments were 15% higher in relation of grain production than fungicide. The C. citratus and C. longa, both with 5%, and the chemical reduced the severity of late season diseases. The better control of powdery mildew was with extract of C. citratus and R. officinalis at 5%, C. longa at 5 and 10% and the fungicide. R. officinalis and C. longa at concentration of 5% were statistically different in relation to enzymatic peroxidase activity, however lesser the control with water. These results indicate that in spite of reducing diseases severity in soybean with the use of C. longa, C. citratus and R. officinalis extracts, this is have not relations with a probably activation of peroxidase activity and that, possibly, other plant defense mechanisms, or a direct antimicrobial activity, maybe envolved in the control of late season leaf disease and powdery mildew